PREVENTIVE MAINTENANCE PADA SLAG HAULER DENGAN METODE REALIBILITY CENTERED MAINTENANCE (RCM) DAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) - Mirpan; Suhariyanto (Rekayasa Sistem Energi dan Manufaktur (ReSEM), 2026)
In the smelter industry, the reliability of heavy equipment such as slag haulers significantly impacts production continuity. Failure of this equipment can lead to high downtime and potentially significant losses. This study aims to improve the effectiveness of slag hauler maintenance by applying the Reliability-Centered Maintenance (RCM) and Failure Mode and Effect Analysis (FMEA) methods to the SH-001 unit.The study was conducted by collecting downtime data and component failure history from the maintenance team over a 3,600-hour operating period. RCM analysis was used to determine maintenance strategies based on function and failure consequences, while FMEA was used to identify failure modes and calculate the Risk Priority Number (RPN) as the basis for maintenance priorities. Reliability calculations were performed using an exponential distribution approach using the Mean Time To Failure (MTTF) and failure rate (λ) distribution.The results showed that the critical components causing downtime were the Fuel Injector Spring, Tensioner Bearing, and Cabin Cylinder O-Ring Seal, contributing more than 65% of the total downtime. The average reliability value for the SH-001 unit after 1,000 hours of operation was 66%. Based on the calculations, the optimal Preventive Maintenance (PM) interval for the Fuel Injector Spring was 1,819 hours, the Tensioner Bearing 1,271 hours, and the Cabin Cylinder O-Ring Seal 1,371 hours. The FMEA results showed the highest RPN values ​​for the Fuel Injector Spring (32), the Tensioner Bearing (24), and the cabin cylinder O-ring seal (16). The recommended RCM-based maintenance strategy covers three main categories: Scheduled Restoration Tasks for periodic replacement of major components, On-Condition Tasks for hydraulic system leak inspections, and Failure Finding Tasks for electrical component and protection system inspections. Implementing this strategy is expected to reduce downtime by up to 30%, increase equipment avalability above 90%, and reduce reactif maintenance costs by 20-25%.